The Determining Factor of Green Personal Care Products Repurchase Decision in the Jakarta Vegetarian Community - Thanra, Divya; Siswantini, Siswantini; Anindita, Kanya; Rajasa, Farasiva Indiani (CV. Utility Project Solution, 2023)
Purpose: This study endeavours to analyse the determining factors that underpin the Jakarta Vegetarian Community's Repurchase Intention Toward Green Personal Care Products. The acquisition of this study bears paramount significance for not only the green marketing field but also for the broader field of environmental communication, which is increasingly reliant on a nuanced understanding of consumer behaviour. Research design, data and methodology: This research was conducted with a quantitative approach that involves testing hypotheses, and survey data collection procedures employing research instruments in the form of questionnaires with the ultimate purpose of testing predetermined hypotheses. Results: 1. Environmental consciousness was the most salient factor in a repurchase decision. Conclusion: This study illustrates that consumers' environmental consciousness plays a pivotal role in motivating them to repurchase green personal care products, primarily due to their recognition that green products play a fundamental role in enhancing the quality of life by minimising pollution, which non-green products tend to contribute to.